Brainstem GLP-1 signalling contributes to cancer anorexia-cachexia syndrome in the rat. (15th March 2018) - Borner, Tito; Liberini, Claudia G.; Lutz, Thomas A.; Riediger, Thomas
Abstract: The cancer anorexia-cachexia syndrome (CACS) is a frequent and severe condition in cancer patients. Currently, no pharmacological treatment is approved for the therapy of CACS. Centrally, glucagon-like peptide-1 (GLP-1) is expressed in the nucleus tractus solitarii (NTS) and is implicated in malaise, nausea and food aversion. The NTS is reciprocally connected to brain sites implicated in the control of energy balance including the area postrema (AP), which mediates CACS in certain tumour models. Given the role of GLP-1 as a mediator of anorexia under acute sickness conditions, we hypothesized that brainstem GLP-1 signalling might play a role in the mediation of CACS. Using hepatoma tumour-bearing (TB) rats, we first tested whether the chronic delivery of the GLP-1R antagonist exendin-9 (Ex-9) into the fourth ventricle attenuates CACS. Second, we investigated whether a genetic knockdown of GLP-1 expression in the NTS ameliorates CACS. Ex-9 attenuated anorexia, body weight loss, muscle and fat depletion compared to TB controls. Similarly, TB animals with a knockdown of GLP-1 expression in the NTS had higher food intake, reduced body weight loss, and higher lean and fat mass compared to TB controls. Our study identifies brainstem GLP-1 as crucial mediator of CACS in hepatoma TB rats. The GLP-1R represents a promising target against CACS and possibly other forms of disease-related anorexia/cachexia. Highlights: Pharmacological blockade of central GLP-1 receptors attenuates CACS in rats. GLP-1-ergic neurons of the nucleus tractus solitarii mediate CACS. Central GLP-1 signalling contributes to loss of lean mass and muscle wasting. GLP-1 receptor antagonists might be therapeutically useful for the treatment of CACS.